The soft multi-legged robot inspired by octopus: climbing various columnar objects. (1st September 2020) - Ito, Kazuyuki; Homma, Yoshihiro; Rossiter, Jonathan
Abstract : In this paper, we develop a soft climbing robot made of silicone. Octopus-like behaviour is realized by a simple mechanism utilizing the dynamics of the soft body, and the robot can grasp various objects of unknown shape. In addition, by inching its truck, it can climb various columnar objects. Experiments, using pipes, long balloons, and natural trees, are conducted to evaluate the effectiveness of the proposed robot. GRAPHICAL ABSTRACT: UF0001